The Analysis of Batata Sentence of Ciacia Language in Traditional Medicine - Husni, Husni (e-Journal of Linguistics; Vol 17 No 1 (2023): ejl-January, 2022)
Batata is one of the aspect of mantras lyrical that lexically can be understood and its contextual meaning based on the necessity. Batata sentence in traditional medicine has not been conducted yet. It is the one of various linguistic aspects. The study present deals with the sentence analysis of batata in traditional medicine of Ciacia language. It has main objectives is formulating and analyzing types of sentences batata in Ciacia language. This is a kind of descriptive-qualitative research which employs a distributional method in data analysis with the underlying theories of syntax. The data taken from informan directly when he has been acted patient treatment for the several times. The result of this study, it found that sentence of batata is filled by Imperative sentences filled by the swear marker consists of pindongo ‘hear’ + S + P + O and compound sentences consist of two clause and four clause. It can be formulated syntactically [if + S + P + Pel] as first clause, while [S + P] as second clause, and [if + P- (no) as first clause, while [S + P] [S + P] [S + P] as second, third, fourth clause .